Posttraumatic Carotid Cavernous Fistula–A Rare Case - Dahiya, Amit; Dahiya, Sumit; Kumar S, Suresh; Rege, Shrikant V; Jatav, Gaurav; Chaitanya, Krishna; Varma, Sandeep (Indian Journal of Neurotrauma, 2020)
Carotid cavernous fistula (CCF) is a specific type of dural arteriovenous (AV) fistula characterized by abnormal AV shunting within the cavernous sinus. The authors presented in this article a case of a 17-year-old young male patient who encountered a road traffic accident while driving a car, with a history of flipping of cars multiple times. The patient was unconscious with symmetrical bilateral (B/L) pupils and with Glasgow coma scale (GCS) score of 3. There was no history of seizures or vomiting.
Keywords: CCF; head injury; posttraumatic pulsating proptosis; posttraumatic carotid cavernous fistula; proptosis